O erótico em Adélia Prado e Marcella Althaus-Reid: uma proposta de diálogo entre poesia e teologia - Boehler, Genilma (2010)
This is a study that aims at reading the poetic and prosaic work of Adélia Prado by choosing the feminist and queer theology of Marcella Althaus-Reid to unveil the relationship between literature and theology in the combination of the erotic and theological elements present in the work of the two authors. Certainly this subject has not been arbitrarily chosen, since God and God's representation in the erotic perspective are very present in the texts of Adélia Prado, combining the biblical, the theological, the religious with the body, the erotic, the sensual, which coincides, in another format, with the theology of Althaus-Reid. Therefore, the text of Prado insinuates the hermeneutical method which favors a poetic interpretation of the texts according to the theology of Althaus-Reid. Another relevant factor that led to the choice of the erotic as interpretive pattern lies in the emancipating element of women, in which the dimension of sexuality has occupied an important space in the feminist struggle for liberation. In this work we will also search for the conceptual elucidation of three distinct situations: poetry, theology, and feminist and queer theories, which are set in dialogue, and search for meaning among them, metaphorically speaking, proposing a dialog between this triad, possibly revealing points of intersection. To analyze the poetic production of Adélia Prado in this perspective will signify a hermeneutical exercise in the perspective proposed by Althaus- Reid, a modern and contemporary theologian.